1998
DOI: 10.1093/treephys/18.4.243
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal fluctuations of starch in root and stem tissues of coppiced Salix viminalis plants grown under two nitrogen regimes

Abstract: Seasonal changes in starch were studied at the tissue and cellular levels in roots and stems of Salix viminalis L. cuttings. Cuttings were planted in pots containing sand and grown in a controlled environment chamber in which seasons were artificially induced by changes in temperature and photoperiod. Nitrogen was supplied at optimum and low rates, and during dormancy, one-half of the plants were decapitated. Starch concentrations in root and stem tissues were determined regularly during shoot extension growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
1

Year Published

2003
2003
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(28 citation statements)
references
References 27 publications
3
24
1
Order By: Relevance
“…By contrast, soluble sugar concentrations were not affected by time or N supply. The relationship between autumn N uptake and TNC accumulation is still debated in the literature, and contrasting results have been published, sometimes relative to the same species (Bollmark et al 1999;Von Fircks and Sennerby-Forsse 1998;Cheng et al 2004).…”
Section: Uptakementioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, soluble sugar concentrations were not affected by time or N supply. The relationship between autumn N uptake and TNC accumulation is still debated in the literature, and contrasting results have been published, sometimes relative to the same species (Bollmark et al 1999;Von Fircks and Sennerby-Forsse 1998;Cheng et al 2004).…”
Section: Uptakementioning
confidence: 99%
“…Most studies to date have been limited to one of these aspects and have not provided an integrated insight into the tree response to N fertilisation. Tree response to applied N varies with tree N status, a point that was not adequately addressed by many prior experiments (Niederholzer et al 2001;Millard and Proe 1993) and could explain inconsistencies in the literature (Bollmark et al 1999;Niederholzer et al 2001;Von Fircks and Sennerby-Forsse 1998). Nitrogen status altered N uptake (Cheng et al 2002), TNC (Total Non structural Carbohydrates) accumulation (Cheng et al 2004) and the trade-off between growth and storage (Sanz Perez et al 2007;Gloser et al 2009) which is generally assumed to be mainly determined by plant phenology.…”
Section: Introductionmentioning
confidence: 99%
“…Primary N assimilation into amino acids has demonstrable effects on both N and C metabolism (Coruzzi 2003;Geiger et al 1996). For example, both young apple and willow trees respond to nitrogen application by reduced accumulation of non-structural carbohydrates such as starch (Cheng et al 2004;von Fircks and Sennerby-Forsse 1998). N-modulated gene expression has been well-investigated in the herbaceous plant model Arabidopsis thaliana (Scheible et al 1997;Schleible et al 2004;Wang et al 2003Wang et al , 2004, where it has been shown that genes involved in C metabolism are co-ordinately regulated in response to N availability (Palanchar et al 2004).…”
Section: Introductionmentioning
confidence: 99%
“…However, an N limitation does not only restrict C acquisition but also C expenses, because root respiration is proportional to N uptake (Bloom et al 1992;Reich et al 1998). The final outcome on tree TNC content at leaf fall is still a matter of discussion since contrasting results have been published, sometimes on the same species (Bollmark et al 1999;Von Fircks and Sennerby-Forsse 1998;Cheng and Fuchigami 2000;Cheng et al 2002). It is however admitted that reducing the N supply in autumn will increase the tree TNC content, unless it affects leaf senescence, which was probably the case in our study.…”
Section: Discussionmentioning
confidence: 60%